Characterization and optimization of extracellular enzymes production by Aspergillus niger strains isolated from date by-products - Reda Bellaouchi; Houssam Abouloifa; Yahya Rokni; Amina Hasnaoui; Nabil Ghabbour; Abdelkader Hakkou; Abdelmajid Bechchari; Abdeslam Asehraou (Journal of Genetic Engineering and Biotechnology, 2021)
Abstract Background This work aims to study the optimal conditions of the fermentation culture medium used for the production of extracellular enzymes (amylase, cellulase, lipase, and protease) from previously isolated Aspergillus niger strains in date by-products. Results The five most powerful isolates selected based on the zone of degradation formed on Petri plates by the substrate were subjected to the quantitative evaluation of their enzymatic production. All five strains showed almost similar API-ZYM profiles, with minor variations observed at the level of some specific enzyme expression. The production of cellulase and amylase was depending on pH and incubation temperatures. ASP2 strain demonstrated the high production rate of amylase (at pH 5 and 30 °C) and cellulase (at pH 6 and 30 °C) for 96 h of incubation. Conclusion The A. niger showed the ability to produce several extracellular enzymes and can be used in the valorization of different agroindustrial residues.